“Our Side of The Story”: Nurses’ Behaviour Towards Patients - Kodom, P.N.B. (University of Ghana, 2023)
The nursing profession is a critical component of healthcare delivery systems, playing an irreplaceable role in patient recovery through the provision of quality care. Rooted in principles of empathy, compassion, trust, and strong interpersonal relationships, nursing is expected to uphold high ethical standards. However, numerous media and empirical reports highlight behaviours among nurses in Ghana, including physical and verbal abuse, neglect, and intolerance towards patients. These behaviours contradict the fundamental tenets established by nursing pioneers like Florence Nightingale and the ethical guidelines of the Ghana Health Service. Given the necessity for quality healthcare in achieving the health-related Sustainable Development Goals by 2030, this study seeks to understand the factors contributing to the general perception of nurses’ behaviours as undesirable. While existing literature has predominantly focussed on patients' perspectives, this research pivots to explore nurses’ experiences and motivations using a qualitative ethnographic approach. The study is framed within several theoretical frameworks, including Blumer’s Symbolic Interactionism, Giddens’ Structuration Theory, Homans’ Rational Choice Theory, Foucault’s Knowledge and Power, and Hochschild’s Emotional Labour. The research was conducted over eleven months in a public district hospital in Accra, Ghana, involving registered nurses with at least one year of experience. A purposive sample of nurses from the medical ward was selected, and data was collected through in-depth interviews, participant observation, focus group discussions, key informant interviews, and informal dialogues, achieving saturation with thirty-two participants. Findings reveal that nurses’ behaviours towards patients are shaped by several precursors, including upbringing and socio-cultural learning. These factors influence their temperaments, communication styles, and values, affecting their professional conduct. The study identifies that nurses motivated by altruism tend to display more desirable behaviours, while those entering the profession for economic reasons or due to familial expectations often struggle to align with nursing's caring ethos. Additionally, the research highlights how power dynamics within the healthcare system contribute to undesirable behaviours, with junior nurses often experiencing abuse of power from senior colleagues, leading to a cycle of negative interactions. Social and structural pressures also play a significant role in shaping nurses’ behaviours. Participants reported that frustrations stemming from patient anxieties, non-cooperation, and interpersonal conflicts significantly affect their behaviour. Institutional factors, such as inadequate resources and poor working conditions, further exacerbate stress and dissatisfaction among nurses, leading to diminished job commitment and increased turnover intentions. Moreover, the emotional toll of the profession, characterised by high levels of distress and psychological hazards, contributes to negative behaviours toward patients. These findings have profound implications, suggesting nurses' behaviours influence patient care quality. The study underscores the need for institutional reforms to enhance communication skills, emotional well-being, and support for nurses. Recommendations include regular training focussed on psychological resilience, fostering collaborative environments, and addressing power dynamics among healthcare providers. Additionally, the research calls for improved resource allocation and a review of nurses’ salaries and working conditions to enhance job satisfaction. In conclusion, this study illuminates the complex interplay of individual motivations, social dynamics, and structural constraints that influence nurses’ behaviours toward patients. By addressing these challenges, healthcare systems can improve patient experiences, retain nursing professionals, and ultimately contribute to achieving the health-related Sustainable Development Goals.
PhD. Sociology
Keywords: nursing profession; f healthcare delivery systems; Ghana